Intelligent Analysis and Evaluation Method of Athletics Running Data Based on Big Data Statistical Model - Ge, Yushan (Mathematical problems in engineering, 2022)
To investigate the effectiveness of pedometry in athletics at different running speeds and on different walking surfaces, and to test whether it can be used for running for fitness and for pedometry on hardened concrete surfaces in daily life. The steps were measured under laboratory conditions using a running platform at 5 min at 5 speeds of 3.2 km/h, 4.8 km/h, 6.4 km/h, 8.0 km/h, and 9.6 km/h (actual steps were accurately determined by video playback), followed by 300 steps each at low, normal and fast speeds on an outdoor plastic athletics track. There were significant differences between the smart bracelet and the mobile phone sports app at low running speeds on four different surfaces: outdoor plastic track, dirt, concrete and mountainous terrain. The difference was not significant in normal pace and fast walking.